Anomalous gold contents in brown coals and peat in the south-eastern region of the Western-Siberian platform - Arbuzov S. I. Sergei Iwanowitsch; Rikhvanov L. P. Leonid Petrovich; Maslov S. G. Stanislav Grigorevich; Arhipov (Arkhipov) V. S. Viktor Sergeyevich; Belyaeva А. M. (2006, 2006)
Title screen